ZOOVI : A PROCESS OF CHANGE - Nadia Jihan Fadila; Devi Novitasari; Hafizh Garda Utama; Luthfi Suwandono; Muhammad Rifki; Zaki Mulya Fadhlurrahman (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Changes made to improve the performance of the previously running system. The purpose of this study was to determine the effect of the COVID-19 pandemic and the process of change that is being pursued by the Bandung Zoo in order to increase the comfort of visitors and animals at the Bandung Zoo on employees, the community, and traders. The research method used is a qualitative research method with an analytical descriptive approach. In this study, a description of the results of observing the situation directly was carried out which was then followed by an analysis based on the results of interviews obtained from related subjects. The results showed that employees, the community, and traders felt a very significant impact from the process of change (development) of the Bandung Zoo coupled with the COVID-19 pandemic. The impact that is felt through the efforts to develop this zoo arises because of the lack of clear communication between the Bandung Zoo and other related subjects.